2011
DOI: 10.1007/s00441-011-1166-x
|View full text |Cite
|
Sign up to set email alerts
|

New components of the Golgi matrix

Abstract: The eukaryotic Golgi apparatus is characterized by a stack of flattened cisternae that are surrounded by transport vesicles. The organization and function of the Golgi require Golgi matrix proteins, including GRASPs and golgins, which exist primarily as fiber-like bridges between Golgi cisternae or between cisternae and vesicles. In this review, we highlight recent findings on Golgi matrix proteins, including their roles in maintaining the Golgi structure, vesicle tethering, and novel, unexpected functions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 152 publications
(192 reference statements)
1
34
0
Order By: Relevance
“…Golgi membranes form a unique stacked structure. This structure is maintained by Golgi structural proteins (11,12), and Golgi fragmentation may be caused by a modification of these proteins, as has been suggested by Sun et al (13). In that study, the authors showed that cyclin-dependent kinase-5 (cdk5) is activated by the addition of synthetic Aβ peptides into the tissue culture medium, which subsequently phosphorylates GM130 and causes Golgi fragmentation.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Golgi membranes form a unique stacked structure. This structure is maintained by Golgi structural proteins (11,12), and Golgi fragmentation may be caused by a modification of these proteins, as has been suggested by Sun et al (13). In that study, the authors showed that cyclin-dependent kinase-5 (cdk5) is activated by the addition of synthetic Aβ peptides into the tissue culture medium, which subsequently phosphorylates GM130 and causes Golgi fragmentation.…”
mentioning
confidence: 63%
“…Formation of the highly organized stacked Golgi structure is mediated by Golgi structural proteins (12), including GRASP65 (25), GRASP55 (26), GM130 (16), golgin-160 (27), and p115 (28). Among these proteins, GRASP65 and GRASP55 play essential roles in Golgi structure formation, whereas the others are important for trafficking across the Golgi stack.…”
Section: Aβ Treatment Causes Golgi Fragmentation In Hippocampal Neuromentioning
confidence: 99%
“…This matrix is necessary for tethering transport vesicles as well as for maintenance of cisternal associations both longitudinally within mini-stacks and laterally between mini-stacks[103]. Made up primarily of peripheral membrane proteins in the GRASP and golgin families, the matrix is highly dynamic as these coiled-coil proteins associate and disassociate both with the Golgi and with each other, in part controlled by well-known kinase pathways[104].…”
Section: Golgimentioning
confidence: 99%
“…Such molecular rulers could include structures, such as the putative spindle matrix (Schweizer et al 2014) and Golgi matrix (Xiang and Wang 2011), which have been proposed to be composed of complex molecular networks. Although these structures are presumably subject to size control and, at least in the case of the spindle matrix, also subject to cell-size-dependent scaling, we know little about how their size is controlled and even less about how their size is scaled appropriately to the size of the cell.…”
Section: Intracellular Scaling Mechanisms Molecular Rulersmentioning
confidence: 99%